Chronic Painful Osteoporotic Vertebral Compression Fractures (OVCFs) of Thoracolumbar Spine: Percutaneous Vertebroplasty versus Conservative Management among Egyptian Patients. Issue 1 (April 2016) - Hasan, Khaled; El-Sharkawi, Mohammad
Introduction: Vertebral augmentation procedures are widely used today in treating Osteoporotic vertebral compression fractures (OVCFs) especially in acute and subacute fractures. However, percutaneous vertebroplasty for patients with chronic painful OVCFs has been less well studied. The purpose of this study is to compare the efficacy and safety of percutaneous vertebroplasty with conservative management for the treatment of chronic painful OVCFs in the thoracolumbar spine among Egyptian patients. Patients and Methods: This prospective cohort study included 60 patients with chronic OVCFs (38 females, 22 males, mean age: 65.42 ± 8.63) who presented with severe back pain to the outpatient clinic during the period from October 2005 to December 2011. Twenty-eight patients were treated with percutaneous vertebroplasty (vertebroplasty group). Thirty two patients refused surgical treatment and constituted the control group (Conservative group). The inclusion criteria included: Chronic painful OVCFs (at least 3 months), at least 50 years old, T5 to L5, osteoporosis (T-score -2.5 or lower), Visual Analogue Scale (VAS) at least 5, and absence of neurological deficits. At presentation, all patients of both groups received back brace, analgesics, anti-osteoporosis therapy. All patients were evaluated with X-rays and CT scan, where Cobb angle and the anteroposterior height comparison (APHC) were measured. Overall pain and quality of life were assessed with the Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI). Results: All patients were followed for at least 12 months (range, 12 to 28). Statistical analysis of the demographic data of the two groups could not reveal any significant differences. At latest follow up, there was significant improvement in Cobb angle and APHC in vertebroplasty group compared with conservative group ( p  < 0.05). Twenty nine patients (90.63%) showed complete union in the conservative group while all patients (100%) showed complete union in the vertebroplasty group at latest follow up. VAS and ODI were significantly better in vertebroplasty group than conservative group ( p  < 0.05) at latest follow up. Cement extravasation into the disc occurred in 2 patients (5.41%), and into the paravertebral tissue in 3 (8.11%); none was associated with neurological symptoms, cement embolism, or infection. Recent fracture occurred adjacent to the formerly cemented ones in 2 patients (7.14%) and in non-adjacent level in one (3.57%). In conservative group, 3 patients (9.37%) presented with new osteoporotic vertebral fractures in adjacent levels and 2 (6.25%) in non adjacent levels. Three patients (9.37%) showed non union. Conclusion: Percutaneous vertebroplasty is safe and effective in treatment of symptomatic chronic osteoporotic vertebral compression fractures with significantly better clinical and radiological outcomes when compared with conservative management.